Barrier-Independent, Fitness-Associated Differences in Sofosbuvir Efficacy against Hepatitis C Virus - Gallego, Isabel (Antimicrob Agents Chemother, 2016)
Sofosbuvir displays a high phenotypic barrier to resistance, and it is a component of several combination therapies for hepatitis C virus (HCV) infections. HCV fitness can be a determinant of decreased sensitivity to direct-acting antiviral agents such as telaprevir or daclatasvir, but fitness-dependent decreased drug sensitivity has not been established for drugs with a high phenotypic barrier to resistance. Low- and high-fitness HCV populations and biological clones derived from them were used to infect Huh-7.5 hepatoma cells. Sofosbuvir efficacy was analyzed by measuring virus progeny production during several passages and by selection of possible sofosbuvir resistance mutations determined by sequencing the NS5B-coding region of the resulting populations. Sofosbuvir exhibited reduced efficacy against high-fitness HCV populations, without the acquisition of sofosbuvir-specific resistance mutations. A reduced sofosbuvir efficacy, similar to that observed with the parental populations, was seen for high-fitness individual biological clones. In independently derived high-fitness HCV populations or clones passaged in the presence of sofosbuvir, M289L was selected as the only substitution in the viral polymerase NS5B. In no case was the sofosbuvir-specific resistance substitution S282T observed. High HCV fitness can lead to decreased sensitivity to sofosbuvir, without the acquisition of specific sofosbuvir resistance mutations. Thus, fitness-dependent drug sensitivity can operate with HCV inhibitors that display a high barrier to resistance. This mechanism may underlie treatment failures not associated with selection of sofosbuvir-specific resistance mutations, linked to in vivo fitness of pretreatment viral populations.